Back Cover: Room‐Temperature Synthesis of Covalent Organic Frameworks with a Boronic Ester Linkage at the Liquid/Solid Interface (Chem. Eur. J. 51/2016). Issue 51 (11th November 2016) - Liu, Chunhua; Yu, Yanxia; Zhang, Wei; Zeng, Qingdao; Lei, Shengbin
Abstract : With various prospected applications in nanoelectronics and catalysis, on‐surface synthesis of single‐layer covalent organic frameworks with designable structures and properties have attracted enormous interest. With the two‐dimensional confinement of a graphite surface, a covalently bonded boronic ester network was synthesized directly at the liquid/solid interface at room temperature. Scanning tunneling microscopy (STM) results indicate that the surface networks undergo structural evolution from a hybrid covalent/noncovalent multiwall porous network to a single‐wall hexagonal covalent organic framework (COF) with the decrease of monomer concentration. More information can be found in the Full Paper by S. Lei et al. onpage 18412 ff.